Peranan Nilai Perusahaan dalam Memoderator Pengaruh Fundamental terhadap Kinerja Keuangan pada Perusahaan Sektor Aneka Industri - Elly Susanti; Khairul Azwar; Christine Dewi Nainggolan (Owner : Riset dan Jurnal Akuntansi, 2021)
IHSG fluctuated from 2015 to 2019 due to the trade war between the U.S. and China resulting in the performance of various industrial sector indices declining. In addition, the factors that cause the decline also come from the company's fundamentals (CR, DAR and TATO) The purpose of this study is to review and analyze the role of the company's value in moderating the fundamental influence of the company on financial performance in multi-industry sector companies recorded in the IDX period 2015 - 2019. The type of research used in this research is quantitative research. The population of 50 issuers uses purposive sampling techniques so that the sample used as many as 19 issuers. Data analysis techniques used are descriptive statistical analysis, classical assumption test, hypothesis test and residual test. The results obtained are known simultaneously the fundamentals of the company (CR, DAR and TATO) have a significant effect. Partially CR and TATO have a positive and significant effect on ROA while DAR has a negative and significant impact on ROA which means that by indicating that the company is able to manage the company's working capital by utilizing the company's assets for operational activities it can improve the company's performance but on the contrary with a high level of debt it will decrease financial performance. While the company's value (PBV) has no role in the influence between the company's fundamentals on financial performance